Diffusion–Perfusion Mismatch: An Opportunity for Improvement in Cortical Function - Motta, Melissa (Front Neurol, 2015)
Objective: There has been controversy over whether diffusion–perfusion mismatch provides a biomarker for the ischemic penumbra. In the context of clinical stroke trials, regions of the diffusion–perfusion mismatch that do not progress to infarct in the absence of reperfusion are considered to represent “benign oligemia.” However, at least in some cases (particularly large vessel stenosis), some of this hypoperfused tissue may remain dysfunctional for a prolonged period without progressing to infarct and may recover function if eventually reperfused. We hypothesized that patients with persistent diffusion–perfusion mismatch using a hypoperfusion threshold of 4–5.9 s delay on time-to-peak (TTP) maps at least sometimes have persistent cognitive deficits relative to those who show some reperfusion of this hypoperfused tissue. Methods: We tested this hypothesis in 38 patients with acute ischemic stroke who had simple cognitive tests (naming or line cancelation) and MRI with diffusion and perfusion imaging within 24 h of onset and again within 10 days, most of whom had large vessel stenosis or occlusion. Results: A persistent perfusion deficit of 4–5.9 s delay in TTP on follow up MRI was associated with a persistent cognitive deficit at that time point (p < 0.001). When we evaluated only patients who did not have infarct growth (n = 14), persistent hypoperfusion (persistent mismatch) was associated with a lack of cognitive improvement compared with those who had reperfused. The initial volume of hypoperfusion did not correlate with the later infarct volume (progression to infarct), but change in volume of hypoperfusion correlated with change in cognitive performance (p = 0.0001). Moreover, multivariable regression showed that the change in volume of hypoperfused tissue of 4–5.9 s delay (p = 0.002), and change in volume of ischemic tissue on diffusion weighted imaging (p = 0.02) were independently associated with change in cognitive function. Conclusion: Our results provide additional evidence that non-infarcted tissue with a TTP delay of 4–5.9 s may be associated with persistent deficits, even if it does not always result in imminent progression to infarct. This tissue may represent the occasional opportunity to intervene to improve function even days after onset of symptoms.